Neuroinflammatory In Vitro Cell Culture Models and the Potential Applications for Neurological Disorders - Ye Peng; Ye Peng; Shifeng Chu; Yantao Yang; Zhao Zhang; Zongran Pang; Naihong Chen; Naihong Chen; Naihong Chen (Frontiers Media S.A., 2021)
Cell cultures are used in pharmaceutical, medical and biological sciences. Due to the ethical and cost limitations of in vivo models, the replaceable cell model that is more closely related to the characteristics of organisms, which has broad prospects and can be used for high-throughput drug screening is urgent. Neuronal and glial cell models have been widely used in the researches of neurological disorders. And the current researches on neuroinflammation contributes to blood-brain barrier (BBB) damage. In this review, we describe the features of healthy and inflamed BBB and summarize the main immortalized cell lines of the central nervous system (PC12, SH-SY5Y, BV2, HA, and HBMEC et al.) and their use in the anti-inflammatory potential of neurological disorders. Especially, different co-culture models of neuroinflammatory, in association with immune cells in both 2D and 3D models are discussed in this review. In summary, 2D co-culture is easily practicable and economical but cannot fully reproduce the microenvironment in vivo. While 3D models called organs-on-chips or biochips are the most recent and very promising approach, which made possible by bioengineering and biotechnological improvements and more accurately mimic the BBB microenvironment.